Full Dynamic Ball Bearing Model with Elastic Outer Ring for High Speed Applications - Christian Wagner; Andreas Krinner; Thomas Thümmel; Daniel Rixen (Lubricants, 2017)
Ball bearings are commonly used in high speed turbomachinery and have a critical influence on the rotordynamic behavior. Therefore, a simulation model of the bearing to predict the dynamic influence is essential. The presented model is a further step to develop an accurate and efficient characterization of the ball bearing’s rotor dynamic parameters such as stiffness and deflections as well as vibrational excitations induced by the discrete rolling elements. To make it applicable to high speed turbomachinery, the model considers centrifugal forces, gyroscopic effects and ball spinning. The consideration of an elastic outer ring makes the bearing model suitable for integrated lightweight bearing constructions used in modern aircraft turbines. In order to include transient rotordynamic behavior, the model is built as a full dynamic multibody simulation with time integration. To investigate the influence of the elasticity of the outer ring, a comparison with a rigid formulation for several rotational speeds and loads is presented.